Sarocladium spinificis: a first report as a causal organism of sheath rot in rice - Bharathi K.B.; Narayanareddy A.B.; Sanath Kumar V.B.; Denesh G.R.; Ashoka K.R.; Kitturmath M.S.; Varshitha S.; Sneha K.B.; Mummineni Sunitha; Akash Bevanur; Supriya S.; Sanju Jalli; et al. (Phytoparasitica, 2026)

Development of Indirect Tensile Strength (ITS) model and resilient modulus assessment considering moisture conditions on bituminous mixtures - A. Jegan Bharath Kumar; V. Sunitha; R. T. Arjun Siva Rathan; Samson Mathew (Innovative Infrastructure Solutions, 2026)

Optimizing Water Productivity in Cassava Production: Comparative Water Footprint of Drip and Furrow Irrigation in Humid Tropics of India - S. Sunitha; A. U. Akash; J. Suresh Kumar; R. Saravanan (Irrigation and Drainage, 2025)
Efficient irrigation strategies are essential for optimizing water use in cassava production. This study evaluated the water footprint of cassava under five irrigation regimes—drip irrigation at 100%, 80% and 60% of crop evapotranspiration (ETc), furrow irrigation, and rainfed conditions—using field data from 2008 to 2012 validated with 2021–2023 data from humid tropical India. The crop ETc showed a decreasing trend, peaking at 378.8 mm in 2008–2009 and reaching its lowest value (307.6 mm) in 2021–2022. Drip irrigation at 100% ETc significantly reduced water use and blue water dependency compared to furrow irrigation, which exhibited high inefficiencies due to surface evaporation and runoff. The blue water usage under furrow irrigation (7200 m 3 in 2021–2023) was reduced to 2065 m 3 with drip irrigation. This efficiency resulted in higher cassava yields, with drip irrigation at 100% ETc achieving the highest yields (45.5 ± 7.3 t ha −1 in 2008–2012 and 46.7 ± 3.5 t ha −1 in 2021–2023), surpassing furrow (~26%–27% lower) and rainfed (~59% lower) conditions. Drip irrigation also led to the lowest total water footprint (80.9 ± 7.0 m 3 t −1 ), representing a 65% reduction compared with furrow irrigation and a 28% reduction compared with rainfed conditions (112.2 m 3 t −1 ). These findings provide crucial insights for sustainable cassava intensification.

OsHV-1 Promoter-driven Transgene Expression in Bivalve Cells: An In Vitro Study with an EGFP-tagged Oncogenic H-RasV12 - Soumya Balakrishnan; Ambadi Kannan Maliyekkal Sajeevan; R. Namitha; M. R. Sunitha; A. Muneer; I. S. Bright Singh; Jayesh Puthumana (Environmental Management, 2025)

Estimation of YOLO algorithms for extracting traffic data using UAV and stationary camera - M. Manjusha; R. Niveditha; V. Sunitha (Innovative Infrastructure Solutions, 2025)

Chandra’s surface thermophysical experiment (ChaSTE) onboard Chandrayaan 3 Lander - Nizy Mathew; K. Durga Prasad; Dinakar Prasad Vajja; V. Aasik; Fazil Mohammad; P.P. Pramod; M. Satheesh Chandran; Kiran John Antony; M. Ram Prabhu; M.B. Dhanya; Manu V. Unnithan; Shiju G. Thomas; et al. (Advances in Space Research, 2025)

Harnessing the power of genomics to develop climate-smart crop varieties: A comprehensive review - K.T. Ravikiran; R. Thribhuvan; C. Anilkumar; Jayanth Kallugudi; N.R. Prakash; Sandeep Adavi B; N.C. Sunitha; Krishnan P. Abhijith (Journal of Environmental Management, 2025)

Genetic enhancement of reproductive stage drought tolerance in RPHR-1005R and derivative rice hybrids through marker-assisted backcross breeding in rice (Oryza sativa L.) - N. Sravanraju; P. Beulah; V. Jaldhani; P. Nagaraju; A. S. HariPrasad; P. Brajendra; N. Sunitha; R. M. Sundaram; P. Senguttuvel (Molecular Biology Reports, 2024)

Role of surface and sub-surface ocean parameters on cyclonic storms over Arabian Sea in the recent decades - A. Amasarao; P. Sunitha; S. R. Rao; K. Chandra sekhar; B. Mmame (Natural Hazards, 2024)

Arctic–midlatitude–tropics interactions in January 2020: linkages to precipitation extremes over Indian region - S. D. Sanap; M. Mohapatra; D. R. Pattanaik; S. Sunitha Devi; Satendra Kumar; A. Kashyapi (Meteorology and Atmospheric Physics, 2024)

Focused identification of germplasm strategy (FIGS): a strategic approach for trait-enhanced pre-breeding - N. C. Sunitha; M. D. Prathibha; R. Thribhuvan; B. M. Lokeshkumar; P. S. Basavaraj; H. C. Lohithaswa; C. Anilkumar (Genetic Resources and Crop Evolution, 2024)

Simultaneous AC/DC distribution for the sustainable operation of smart building clusters in hybrid urban microgrids - T.P. Vishnu; Gopakumar P; Sunitha R (Energy and Buildings, 2023)

Corrigendum to “Sphingomonas pokkalii sp. nov., a novel plant associated rhizobacterium isolated from a saline tolerant pokkali rice and its draft genome analysis” [Syst. Appl. Microbiol. 42(3) (2019) 334–342] - Rahul R. Menon; Sunitha Kumari; Pravin Kumar; Ashish Verma; Srinivasan Krishnamurthi; N. Rameshkumar (Systematic and Applied Microbiology, 2023)

Metabolite Effect on Angiogenesis: Insights from Transcriptome Analysis - P. Sunitha; Kesavan R. Arya; Achuthsankar S. Nair; Oommen V. Oommen; Perumana R. Sudhakaran (Cell Biochemistry and Biophysics, 2022)

Yield Estimation of Cassava Using SIMCAS Model Over the Major Cassava Growing Regions in India - Divya K. Lekshmanan; Raji Pushpalatha; V. S. Santhosh Mithra; S. Sunitha; James George; M. Velmurugan; P. Ashok; N. V. Mhasker; K. D. Desai; R. Shiny; Gangadharan Byju (Agricultural Research, 2022)

Discovery of genomic regions associated with resistance to late wilt disease caused by Harpophora maydis (Samra, Sabet and Hing) in maize (Zea mays L.) - N. C. Sunitha; E. Gangappa; R. P. Veeresh Gowda; S. Ramesh; Sunil Biradar; Dharanendra Swamy; H. B. Hemareddy (Journal of Applied Genetics, 2022)

Genetic stock identification in Perna viridis (Linnaeus1758) from the Indian Peninsula by using microsatellite markers - P. R. Divya; Linu Joy; Sunitha Poulose; P. M. Elizabeth Jency; V. S. Basheer; A. Kathirvelpandian; Vindhya Mohindra; Kuldeep Kumar Lal (Molecular Biology Reports, 2022)

Testing of Cassava (Manihot esculenta) Varieties for Climate Resilience Under Kerala (India) Conditions - Raji Pushpalatha; R. Shiny; Govindan Kutty; V. K. Dua; S. Sunitha; V. S. Santhosh Mithra; G. Byju (Agricultural Research, 2022)

ENIGMA + COINSTAC: Improving Findability, Accessibility, Interoperability, and Re-usability - Jessica A. Turner; Vince D. Calhoun; Paul M. Thompson; Neda Jahanshad; Christopher R. K. Ching; Sophia I. Thomopoulos; Eric Verner; Gregory P. Strauss; Anthony O. Ahmed; Matthew D. Turner; Sunitha Basodi; Judith M. Ford; et al. (Neuroinformatics, 2022)
The FAIR principles, as applied to clinical and neuroimaging data, reflect the goal of making research products F indable, A ccessible, I nteroperable, and R eusable. The use of the Collaborative Informatics and Neuroimaging Suite Toolkit for Anonymized Computation (COINSTAC) platform in the Enhancing Neuroimaging Genetics through Meta-Analysis (ENIGMA) consortium combines the technological approach of decentralized analyses with the sociological approach of sharing data. In addition, ENIGMA + COINSTAC provides a platform to facilitate the use of machine-actionable data objects. We first present how ENIGMA and COINSTAC support the FAIR principles, and then showcase their integration with a decentralized meta-analysis of sex differences in negative symptom severity in schizophrenia, and finally present ongoing activities and plans to advance FAIR principles in ENIGMA + COINSTAC. ENIGMA and COINSTAC currently represent efforts toward improved Access, Interoperability, and Reusability. We highlight additional improvements needed in these areas, as well as future connections to other resources for expanded Findability.

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Efficacy of Indolicidin, Cecropin A (1-7)-Melittin (CAMA) and Their Combination Against Biofilm-Forming Multidrug-Resistant Enteroaggregative Escherichia coli - Jess Vergis; S. V. S. Malik; Richa Pathak; Manesh Kumar; R. Sunitha; S. B. Barbuddhe; Deepak B. Rawool (Probiotics and Antimicrobial Proteins, 2020)

Role of enhanced synoptic activity and its interaction with intra-seasonal oscillations on the lower extended range prediction skill during 2015 monsoon season - S. Abhilash; R. Mandal; A. Dey; R. Phani; S. Joseph; R. Chattopadhyay; S. De; N. K. Agarwal; A. K. Sahai; S. Sunitha Devi; M. Rajeevan (Climate Dynamics, 2018)

Occurrence and Antibiotic Susceptibility Testing of Vibrio cholerae from District Wayanad, Kerala, India - Ebin Baby Mathews; B. Sunil; N. Prejit; C. Sunanda; V. K. Vinod; Jess Vergis; K. Asha; R. Sunitha (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Design, synthesis, and cytotoxicity evaluation of threonine-based galactoceramide with aromatic groups and various fatty-acyl side chains - Srikanth Vudhgiri; Sunitha Rani Routhu; C. Ganesh Kumar; R. B. N. Prasad; Ram Chandra Reddy Jala (Medicinal Chemistry Research, 2018)

The contribution of trees to ecosystem methane emissions in a temperate forested wetland - Sunitha R. Pangala; Edward R.C. Hornibrook; David J. Gowing; Vincent Gauci (Global Change Biology, 2015)
Wetland‐adapted trees are known to transport soil‐produced methane ( CH 4 ), an important greenhouse gas to the atmosphere, yet seasonal variations and controls on the magnitude of tree‐mediated CH 4 emissions remain unknown for mature forests. We examined the spatial and temporal variability in stem CH 4 emissions in situ and their controls in two wetland‐adapted tree species ( Alnus glutinosa and Betula pubescens ) located in a temperate forested wetland. Soil and herbaceous plant‐mediated CH 4 emissions from hollows and hummocks also were measured, thus enabling an estimate of contributions from each pathway to total ecosystem flux. Stem CH 4 emissions varied significantly between the two tree species, with Alnus glutinosa displaying minimal seasonal variations, while substantial seasonal variations were observed in Betula pubescens . Trees from each species emitted similar quantities of CH 4 from their stems regardless of whether they were situated in hollows or hummocks. Soil temperature and pore‐water CH 4 concentrations best explained annual variability in stem emissions, while wood‐specific density and pore‐water CH 4 concentrations best accounted for between‐species variations in stem CH 4 emission. Our study demonstrates that tree‐mediated CH 4 emissions contribute up to 27% of seasonal ecosystem CH 4 flux in temperate forested wetland, with the largest relative contributions occurring in spring and winter. Tree‐mediated CH 4 emissions currently are not included in trace gas budgets of forested wetland. Further work is required to quantify and integrate this transport pathway into CH 4 inventories and process‐based models.

An overview on genus garcinia: phytochemical and therapeutical aspects - M. Hemshekhar; K. Sunitha; M. Sebastin Santhosh; S. Devaraja; K. Kemparaju; B. S. Vishwanath; S. R. Niranjana; K. S. Girish (Phytochemistry Reviews, 2011)

Zooplankton community structure across an eddy-generated upwelling band close to a tropical bay-mangrove ecosystem - M. Rakhesh; A. V. Raman; C. Kalavati; B. R. Subramanian; V. S. Sharma; E. Sunitha Babu; Nanduri Sateesh (Marine Biology, 2008)

Ionic liquids as a reaction medium for lipase-catalyzed methanolysis of sunflower oil - S. Sunitha; S. Kanjilal; P. S. Reddy; R. B. N. Prasad (Biotechnology Letters, 2007)